2017
DOI: 10.12659/msm.904087
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MIh Scoring System in Diagnosis of Obstructive Sleep Apnea Syndrome

Abstract: BackgroundThe objective of the present study was to investigate whether the analysis of magnesium (Mg), high-sensitivity C-reactive protein (hsCRP), and ischemia-modified albumin (IMA) concentrations can be used as a non-invasive and convenient method for diagnosing obstructive sleep apnea syndrome (OSAS).Material/MethodsAfter polysomnography, venous blood was collected from 33 patients with OSAS and 30 control individuals. Serum levels of Mg, hsCRP, and IMA were investigated. The relationship between these fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…These levels were significantly lower than the controls (N=30) matched for age, sex and BMI, which showed healthy levels of mean serum Mg serum at 2.19 ± 0.36 mg/dL (p<0.0001). These findings were similar to that of Xu et al [24], where patients with OSA (N=33, 1.71±0.21 mg/dL) had serum Mg levels significantly lower (p=0.021) than those in the control group (N=33, 2.19±0.36 mg/dL). Furthermore, 23 patients (69.7%) in the OSA group demonstrated hypomagnesemia.…”
Section: Comparing To Healthy Controlssupporting
confidence: 91%
See 2 more Smart Citations
“…These levels were significantly lower than the controls (N=30) matched for age, sex and BMI, which showed healthy levels of mean serum Mg serum at 2.19 ± 0.36 mg/dL (p<0.0001). These findings were similar to that of Xu et al [24], where patients with OSA (N=33, 1.71±0.21 mg/dL) had serum Mg levels significantly lower (p=0.021) than those in the control group (N=33, 2.19±0.36 mg/dL). Furthermore, 23 patients (69.7%) in the OSA group demonstrated hypomagnesemia.…”
Section: Comparing To Healthy Controlssupporting
confidence: 91%
“…Five articles were excluded with reasons (Figure 1). Six studies [21][22][23][24][25][26] are included in this systematic review, and five in the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty articles were excluded with reasons ( Figure 1 ). Six studies [ 21 , 22 , 23 , 24 , 25 , 26 ] are included in this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A study including patients with obstructive sleep apnea reported that serum amounts of IMA increased with the presence and severity of disease. [33] It was also reported that increased serum IMA levels might be regarded as a marker of increased tissue hypoxia in patients with acute leukemia. [34] In addition, in recent years, several studies have shown an interest to IMA levels and its possible correlation with diseases such as chronic obstructive pulmonary disease, acute rheumatic fever, and nasal polyposis.…”
Section: Discussionmentioning
confidence: 99%